Identification of Brucella abortus virulence proteins that modulate the host immune response - Wang, Yufei (Landes Bioscience, 2012)
Brucellosis is an important zoonotic disease of almost worldwide distribution. One significant immune phenomenon of this disease is the ability of the pathogen to hide and survive in the host, establishing long lasting chronic infections. Brucella was found to have the ability to actively modulate the host immune response in order to establish chronic infections, but the mechanism by which the pathogen achieves this remains largely unknown. In our screening for protective antigens of Brucella abortus, 3 proteins (BAB1_0597, BAB1_0917, and BAB2_0431) were found to induce significantly higher levels of gamma interferon (IFNγ) in splenocytes of PBS immunized mice than those immunized with S19. This finding strongly implied that these three proteins inhibit the production of IFNγ. Previous studies have shown that LPS, PrpA, and Btp1/TcpB are three important immunomodulatory molecules with the capacity to interfere with host immune response. They have been shown to have the ability to inhibit the secretion of IFNγ, or to increase the production of IL-10. Due to the role of these proteins in virulence and immunomodulation, they likely offer significant potential as live, attenuated Brucella vaccine candidates. Understanding the mechanisms by which these proteins modulate the host immune responses will deepen our knowledge of Brucella virulence and provide important information on the development of new vaccines against Brucellosis.